Toleransi Perspektif KH. M. Hasyim Asy’ari dan Peran Pendidikan Islam Sebagai Upaya Deradikalisasi di Indonesia - Mukani Mukani (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2018)
The diversity value has been an interested discussion in Indonesia. Many groups have made effort to impose their views to be accepted for others that leads to exclusivity and tends to be radical. In this stage, being exclusive to give opinion will be able to be frightening terrorist to society. This article reviews the tolerance (tasamuh) concept initiated by KH. M. Hasyim Asy’ari as an alternative solution as deradicalization effort in Indonesia. This concept is sourced from 23 books and treatises written by Kiai Hasyim. This article positioned the tasamuh concept as pearl when the threat of intolerance has spreaded in this country. The advantage of this concept can be seen the toughness aspect. Kiai Hasyim in this case did not create theory only, he had carried out it consistenly in his daily life. This tasamuh value has been urgently required this nation in spreading the beauty of Islam as rahmatan lil ‘alamin religion. Education has an important role in introducing more closely the tasamuh value initiated Kiai Hasyim to society in the life of nation and religion in Indonesia which known as multicultural nation.